How did China's WTO entry benefit U.S. consumers? - Mary Amiti; Mi Dai; Robert C. Feenstra; John Romalis (Federal Reserve Bank of New York, 2017)
China's rapid rise in the global economy following its 2001 World Trade Organization (WTO) entry has raised questions about its economic impact on the rest of the world. In this paper, we focus on the U.S. market and potential consumer benefits. We find that the China trade shock reduced the U.S. manufacturing price index by 7.6 percent between 2000 and 2006. In principle, this consumer welfare gain could be driven by two distinct policy changes that occurred with WTO entry. The first, which has received much attention in the literature, is the United States granting permanent normal trade relations (PNTR) to China, effectively removing the threat of China facing very high tariffs on its exports to the United States. A second, new channel we identify is China reducing its own input tariffs. Our results show that China's lower input tariffs increased its imported inputs, boosting Chinese firms' productivity and their export values and varieties. Lower input tariffs also reduced Chinese export prices to the U.S. market. In contrast, PNTR had no effect on Chinese productivity or export prices, but did increase Chinese entry into the U.S. export market. We find that at least two-thirds of the China WTO effect on the U.S. price index of manufactured goods was through China lowering its own tariffs on intermediate inputs.
Keywords: F12; F13; F14; 330; China; WTO entry; input tariffs; price index; consumers; WTO-Mitgliedschaft; Vorleistungen; Importbeschränkung; Handelsliberalisierung; Exportpreis; China; Erzeugerpreisindex; Außenhandelspreis; Konsumentenrente; Schätzung; USA